2007
DOI: 10.4049/jimmunol.179.5.2722
|View full text |Cite
|
Sign up to set email alerts
|

PDGF Synergistically Enhances IFN-γ-Induced Expression of CXCL10 in Blood-Derived Macrophages: Implications for HIV Dementia

Abstract: There is increasing cumulative evidence that activated mononuclear phagocytes (macrophages/microglia) releasing inflammatory mediators in the CNS are a better correlate of HIV-associated dementia (HAD) than the actual viral load in the brain. Earlier studies on simian HIV/rhesus macaque model of NeuroAIDS confirmed that pathological changes in brains of macaques with encephalitis were associated with up-regulation of platelet-derived growth factor (PDGF) and the chemokine, CXCL10. Because the complex interplay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 70 publications
3
46
0
Order By: Relevance
“…It is interesting to note that platelet-derived growth factor expression, which is significantly upregulated in the coculture system described above, has been shown to act synergistically with IFN-γ to stimulate CXCL10 expression in other cell systems. 46 In support of our in vitro findings, we have demonstrated that CXCL10 is expressed in α-smooth muscle actin positive cells in first trimester decidual sections. Interestingly, some cells expressing CXCL10 were found at some distance from the vessel lumen.…”
Section: Il-6 Is Expressed In Myometrial Arteriessupporting
confidence: 70%
“…It is interesting to note that platelet-derived growth factor expression, which is significantly upregulated in the coculture system described above, has been shown to act synergistically with IFN-γ to stimulate CXCL10 expression in other cell systems. 46 In support of our in vitro findings, we have demonstrated that CXCL10 is expressed in α-smooth muscle actin positive cells in first trimester decidual sections. Interestingly, some cells expressing CXCL10 were found at some distance from the vessel lumen.…”
Section: Il-6 Is Expressed In Myometrial Arteriessupporting
confidence: 70%
“…These observations are intriguing given the purported role of IFN-␥ in the pathogenesis of several diseases, such as multiple sclerosis, sepsis, human immunodeficiency virus-associated dementia, and Alzheimer's (14,19,32,79,81). The results of the present study can lend insight into results from current clinical trials involving the administration of IFN-␥ as adjuvant therapy (49) and possibly the design of future trials involving IFN-␥ blockade.…”
Section: Discussionmentioning
confidence: 76%
“…TNF␣ and IFN␥ Do Not Regulate CXCL10 via Post-transcriptional Mechanisms-Regulation of CXCL10 has been reported previously to be mediated via both transcriptional and posttranscriptional mechanisms (38); therefore, we investigated whether costimulation with TNF␣ and IFN␥ affect CXCL10 mRNA stability. As can be seen in Fig.…”
Section: Tnf␣ and Ifn␥ Synergistically And Transcriptionallymentioning
confidence: 99%